Courseware development to assist E-learning - Li, Li (2018)
E-learning is the new form of learning method employed with the help of technology, which allows learners to learn at their own pace and time without being in a classroom. This form of learning has been adopted into the mainstream of educational program by many universities. The Courseware Development to Assist E-learning is to develop a methodology of courseware to assist lecturers for Computer Networking course, utilizing computer animation tool Adobe Flash. The goal of this project is to make the content more illustrative to the students, which animations to aid in their understanding. The latest version of Adobe Flash is Adobe Animate CC 2017, which is the software that I used to develop the courseware. This software allows the user to design vector graphics, animation, and publish the same for website, web applications and video games. In the near future, Adobe Flash will not be supported by Windows and other internet browser platform, it is extremely user-friendly for first-timers who has not use the software. The latest version includes a new function that convert flash files into HTML 5. HTML 5 is the fifth and the current major version of HTML standard. Hence, learning how to use flash can be beneficial to anyone.